Mewujudkan Kemandirian UMKM Melalui Pelatihan dan Pendampingan Pencatatan Laporan Keuangan Dan Penetapan Harga Jual Produk - Yulmaini Yulmaini; Sri Lestari; Mieke Rahayu; Aswin Aswin; Fitri Agustina; Sulyono Sulyono; Ruki Rizal Nul Fikri; Ade Moussadecq; Muhammad Redintan Justin (-, 2023)
The Indonesian government has declared Covid-19 as a national disaster since April 13, 2020. Various efforts have been made by the government such as Work From Home (WFH), social distancing, and the Enforcement of Restrictions on Community Activities (PPKM) to reduce the spread of the corona virus. However, this policy has an impact on the decline in people's purchasing power. One of the sectors affected is MSMEs. This service aims to provide assistance in making financial statement bookkeeping and determining product selling prices for MSMEs in Pesawaran Regency. The three stages of activities carried out include preparation, implementation and monitoring. Preparation is carried out by conducting surveys in the field in coordination with partners. The implementation is carried out by training and mentoring using the lecture method followed by a question and answer discussion, and practicing making financial reports and calculating product selling prices. Monitoring is carried out periodically during service activities. This service results in the recording of simple financial statements, namely the cash book, accounts payable book, accounts receivable book, and inventory book, as well as calculating production costs and selling prices (hpp). Knowledge and soft skills regarding financial reports and determining product selling prices for MSME owners are needed, so that their business development can be monitored.